Service Quality and Student Satisfaction: A Case Study of Private External Higher Education Institutions in Jaffna, Sri Lanka - Kajenthiran, K.; Karunanithy, M. (University of Jaffna, 2015)
In today’s aggressive competitive education business world, service quality has become one of the most important determinants of student satisfaction. It has also become the key to sustainable competitive advantage for mainly service providing organizations as well as for the education sector. The purpose of this paper is to empirically investigate the relationship between service quality and student satisfaction in private external higher education institutions in Jaffna. Additionally, this study attempts to examine critical factors in service quality dimensions that contribute most to the satisfaction of the students. The Service quality scale, which comprised of 46 service quality statements under five dimensions namely, tangibility, responsiveness, reliability, assurance and empathy has been used as the data collection instrument. In order to collect primary data, 200 external undergraduate/Professional studies students randomly selected from two private external education service providers in Jaffna.
Keywords: Service quality; Student Satisfaction; Private external higher education institutions; Servqual